Cesarean sections in a secondary level care hospital of Cameroon: an analysis of their six-year trends and adverse neonatal outcomes - Tsi Njim; Simeon-Pierre Choukem; Robinson Mbu (BMC Research Notes, 2017)
Abstract Background The objectives of this study were to determine the trends of CS in a regional hospital in Cameroon and to explore its association with adverse neonatal outcomes. Methods The study was conducted in the Buea Regional Hospital (BRH), Cameroon. A 6-year retrospective records analysis was used to determine the trends in rates of CS and neonatal adverse outcomes. In a 3-month prospective phase, indications of CS were identified. Results Of a total of 4941 records reviewed from the year 2007 to 2012, the overall CS rate was 20.4%. The rates increased from 17.1% in 2007 to 20.9% in 2012, with a peak of 22.7% in 2011, but this time-trend was not significant (p-trend =0.06). Three of the 25 cases of CS (12%) in the prospective phase were done at the request of mothers. The odds of having a low first minute APGAR (APGAR <7) in neonates born from CS were higher than in neonates born from a normal delivery (OR = 6.6 and 95% CI 5.7–7.7; p < 0.01). Conclusion One out of every five women give birth through a CS in the BRH. This rate of CS is relatively high for a suburban population in a developing country. Strategies to reduce these rates should be investigated and instituted in the BRH to reduce health expenditures.